Development of a Microsoft Access-Based Mail Automation System to Improve Student Digital Administration - Atika Salma; Dyah Aulia Rahma; Farida Fatkhur Rohmah; Fitrotul Awaliyah; Hibatullah ‘Aqil Syahrizal; Nina Farliana (Al-Qalam Institue, 2026)
This study aims to develop and evaluate a Microsoft Access-based mail automation system to improve administrative efficiency and students’ digital administration competence. The research employed a Research and Development (R&D) approach adapted from the Borg and Gall model, consisting of needs analysis, product design, expert validation, limited testing, field testing, implementation, and evaluation stages. Data were collected through questionnaires, expert validation sheets, and competency assessments administered before and after system implementation. The results indicated that the developed system was categorized as highly feasible based on expert evaluations in archive management and information technology. Furthermore, students’ digital administration competence increased from a pretest mean score of 3.05 to a posttest mean score of 4.45. Statistical analysis revealed a significant effect of system utilization on competency improvement, with an R² value of 0.512 and p < 0.0001. The system also contributed to reducing administrative errors, accelerating correspondence processes, and improving document organization. These findings imply that mail automation systems can support digital transformation initiatives by strengthening administrative efficiency, technological literacy, and digital competence within student organizations and other educational administrative environments.